ANALISIS HUBUNGAN ANTARA KEMAMPUAN PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH PADA TOPIK VEKTOR DAN SKALAR - Sinaga, Rani Farida (MES: Journal of Mathematics Education and Science, 2024)
One of the minimum learning outcomes of the S1 Mathematics Education study program at HKBP Nommensen University in the knowledge aspect is: P2) mastering mathematical concepts and data information needed to solve problems. This study aims to determine whether there is a relationship between the ability to understand concepts and problem-solving abilities on the topic of vectors and scalars. The type of research used in this study is quantitative research using a descriptive approach and the instrument used is a descriptive test. Data analysis uses correlation tests and coefficients of determination. Based on the results of data analysis in the r statistical test, ????ℎi????????????g = 0.7308 is obtained which shows a significant relationship between the ability to understand concepts and problem-solving abilities on the topic of vectors and scalars. The magnitude of the relationship between the ability to understand concepts and problem-solving abilities on the topic of vectors and scalars is 52%. so it can be concluded that there is a significant relationship between the ability to understand concepts and problem-solving abilities on the topic of vectors and scalars.